Revealing Ravel: la scienza racconta Boléro - Luigi Dei (Electronica, 2014)
Telling music with science. It is the challenging goal behind Revealing Ravel: science tells Bolero, musical piece for reciting voice, multimedia and orchestra on the notes of the French composer. The author and protagonist is Luigi Dei, professor of Chemistry at the Department of Chemistry "Ugo Schiff". Dei deals with an unusual approach with the composition of Maurice Ravel, alongside the Symphonic Orchestra of the Conservatory "Luigi Cherubini", conducted by Maestro Paolo Ponziano Ciardi: for science, in fact, music is energy that propagates through matter thanks to vibrations generated by the instruments which, with appropriate resonances, generate timbres, rhythm, melody and harmony. The Bolero, a piece of music particularly suited to understanding the wonder behind sound production, is read as a fantastic fairy tale. The musical piece, which consolidates the collaboration between two important cultural institutions of the Florentine territory, the University and the Conservatory, combines acting and listening to live communication through images thanks to a multimedia system by the Multimedia Content Production Service of the University.